The Effectiveness of Blended Learning Model to Promote Physics Students’ Critical Thinking Skill - Bahtiar, Bahtiar (Jurnal Pendidikan Indonesia, 2021)
Critical thinking skills that are claimed to be in the medium and low categories require special attention. Efforts that can be made to overcome these problems are to use an explicit learning model to develop students' critical thinking skills by considering the integration of technology in the learning process. This study aimed to describe the validity, practicality, and effectiveness of blended learning model in promoting critical thinking skill. This study garnered the data regarding the validity from three validators. The practicality of the learning model was based on the applicability of the learning model, students’ responses and challenges faced throughout the teaching and learning process; while the effectiveness of the learning model was based on the increase of the critical thinking skill. The empirical evidence showed that the average score given by the three validators was 3.7 with the percentage of 90% reliability, which falls into a very valid category. The blended learning model enabled the students to develop their critical thinking skill with the average achievement 0.83 for each indicator of critical thinking. This study concluded that the blended learning model was valid, practical, and effective to promote students’ critical thinking skill. The results of this study can be used as an alternative solution to improving students' critical thinking skills that are relevant to technological developments.